BENTUK KONTRIBUSI DAYA TARIK WISATA MONKEY FOREST DALAM MENSEJAHTERAKAN MASYARAKAT LOKAL DI DESA PADANG TEGAL KECAMATAN UBUD - Suarmana, I Wayan Restu; Mahagangga, I Gusti Agung Oka (JURNAL DESTINASI PARIWISATA, 2014)
Abstrack The tourist destination of Wanara Wana or better known as the Monkey Forest is a tourist destination which is very famous in Ubud especially in the traditional village of Padang Tegal. Existence Tourist destination of Monkey Forest provide a huge influence for the welfare of the local communities in the traditional village of Padang Tegal. It is seen from the contributions that the Monkey Forest gave to the traditional village of Padang Tegal. That was my Assumptions to choose this research topic "Contribution Travel Attractions Monkey Forest in the welfare of the local communities in the traditional village of Padang Tegal, Ubud District, Gianyar regency" for examination. Types of data and data sources used are the data Qualitative, primary data and secondary data. Data collection by observation, in-depth interviews, documentation, literature study, research instruments such as interview guides. The analysis of data is the analysis of qualitative data is clearly presented findings based on the problems studied by accurate data source. People's perceived contribution to the economy in a society that is ease of development and maintenance costs (temple, bale banjar, infrastructure). Socio-cultural field that consists of the livelihood aspects of community empowerment in the recruitment of staff at Monkey Forest (prioritizing local communities), the education aspect provides scholarships for high achievers, the availability of free tutoring place, aspects of ritual / religion of helping communities in spending during piodalan or mass cremation (making offerings), aspects of art and culture is the availability of free dance classes and percussion performed on banjo and wantilan hall. Environmental field are taught how to maintain natural communities through waste processing equipment provided .
Keywords: Destination, Contribution, and Welfare society